2017
DOI: 10.1007/s10565-017-9383-z
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic study suggesting human iPSC-derived hepatocytes potentially offer a better in vitro model of hepatotoxicity than most hepatoma cell lines

Abstract: Hepatocytes derived from human induced pluripotent stem cells (iPSCs) hold great promise as an in vitro liver model by virtue of their unlimited long-term supply, stability and consistency in functionality, and affordability of donor diversity. However, the suitability of iPSC-derived hepatocytes (iPSC-Heps) for toxicology studies has not been fully validated. In the current study, we characterized global gene expression profiles of iPSC-Heps in comparison to those of primary human hepatocytes (PHHs) and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Though immortalized human cell lines, such as HUH7 and HepG2, as well as iPSC-derived hepatocytes, can be induced towards a steatotic phenotype in culture, multiple studies have shown that these cells poorly represent the native liver metabolic function, thus keeping primary human hepatocytes as the gold standard for in vitro studies [2022]. In addition to hepatocytes, the addition of non-parenchymal cells (NPC), including human hepatic stellate cells (HSCs), resident inflammatory cells (e.g., Kupffer cells, macrophages), and/or sinusoidal endothelial cells (sECs), affect liver biology and are known to contribute to the progression of NAFLD [23–25].…”
Section: Human In Vitro Organotypic Models Of Nafldmentioning
confidence: 99%
“…Though immortalized human cell lines, such as HUH7 and HepG2, as well as iPSC-derived hepatocytes, can be induced towards a steatotic phenotype in culture, multiple studies have shown that these cells poorly represent the native liver metabolic function, thus keeping primary human hepatocytes as the gold standard for in vitro studies [2022]. In addition to hepatocytes, the addition of non-parenchymal cells (NPC), including human hepatic stellate cells (HSCs), resident inflammatory cells (e.g., Kupffer cells, macrophages), and/or sinusoidal endothelial cells (sECs), affect liver biology and are known to contribute to the progression of NAFLD [23–25].…”
Section: Human In Vitro Organotypic Models Of Nafldmentioning
confidence: 99%
“…This may be a reason for the disappointing outcomes of the clinical ELAD trials. Another cell source comprises original or induced stem cells, which, however, display a limited functional spectrum as well [17,24]. To date, the most functional human liver cell line is the HepaRG cell line [25], which further differentiates by culturing in the AMC-BAL system [26].…”
Section: Concluding Remarks Clinically Applied Cell-based Alssmentioning
confidence: 99%
“…To date, the most functional human liver cell line is the HepaRG cell line [25], which further differentiates by culturing in the AMC-BAL system [26]. Comparison of the transcriptomes of different proliferative sources of human liver cells showed that HepaRG cells most closely resembled primary human hepatocytes [24,27]. Further improvement of existing cell systems may be achieved by (conditional) ectopic expression of limiting regulatory or structural genes and by application of cell culture systems promoting maturation, e.g.…”
Section: Concluding Remarks Clinically Applied Cell-based Alssmentioning
confidence: 99%
“…This can provide guidance for researchers in the diverse areas of toxicology research that are interested in applying these new technologies to their own work. Encouragingly, research-based articles also being published in CBT, for example, the application of iPSC and cell reprogramming strategies for predicting drug toxicity Gao and Liu 2017). If CBT can continue to expand its scope to encompass cutting edge technologies, while still providing a highquality resource for toxicology research, we believe the journal can continue to expand and publish high quality research and reviews.…”
Section: Summary and Opinionmentioning
confidence: 99%